Ginzburg‐Landau Model in a Finite Shear‐Layer and Onset of Transport Barrier Nonlinear Oscillations: A Paradigm for TypeIII ELMs. Issue 6 (24th June 2016) - Leconte, M.; Jeon, Y.M.; Yun, G. S.
Abstract: We study a Reaction‐Diffusion model describing the nonlinear oscillations of a transport barrier in a finite shear‐layer (width dE ≪ a ), where a is the plasma minor radius, based on a 1D reduced model derived to explain nonlinear barrier oscillations in 3D turbulence simulations [P. Beyer, S. Benkadda, G. Fuhr‐Chaudier et al., Phys. Rev. Lett.94, 105001 (2005)]. We show that this single nonlinear equation encompasses most of the physics of these barrier relaxations. The nonlinear oscillations have common characteristics with type‐III edge localized modes (ELMs), such as a repetition frequency which decreases with increasing power. In addition to the flow shear, the shear‐layer width is also shown to control the nature of the oscillations. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)